Condensation and evaporation in capillaries with nonuniform cross sections - Fan, Chunyan; Do, D.; Nicholson, D. (2013)
We present a Grand Canonical Monte Carlo simulation study of argon adsorption at 87 K in slit shape mesopores with nonuniform separation between the pore walls. We show that different wall curvatures can generate diverse hysteresis loop shapes, simply by tuning the wall curvature and hence the variation of width along the pore. In this way we are able to describe all the hysteresis loop shapes classified by de Boer in 1972 and later by the IUPAC in 1985, including the de Boer Types C and D, which were omitted from the IUPAC classification. In addition we observe other loop shapes not identified in either classification but which have been reported experimentally. © 2013 American Chemical Society.